The Effect of Joint Audit on Audit Quality: The Perceptions of Accountant Exports and Banking Mangers in Algeria - Hima, Zakaria; Yusoff, Wan Sallha; Saraih, Ummi Naiemah binti (South Asian Journal of Social Sciences and Humanities, 2024)
This study examines the impact of joint audits on audit quality. It employs a survey-based approach, utilizing a Likert-type questionnaire distributed to external auditors and bank managers to gauge their perspectives on whether joint audits enhance audit quality. The survey involved auditors and managers from the Regional Directorate of Exploitation in 20 Algerian banks. The findings indicate a correlation between joint audits and audit quality, with respondents expressing the belief that the implementation of joint audits would positively influence audit quality. This research is one of the pioneering efforts to investigate the effects of joint audits on audit quality within the Algerian banking sector. It offers valuable insights and puts forth recommendations for audit firms, professional and oversight bodies, as well as the government, emphasizing the significance of joint audits in ensuring audit quality.